Effect of 200 MeV Ag+15 ion irradiation on structural, microstructural and dielectric properties of Y0·95Sr0·05MnO3 manganite films. (September 2020) - Gadani, Keval; Rathod, K.N.; Shrimali, V.G.; Rajyaguru, Bhargav; Udeshi, Bhagyashree; Vadgama, V.S.; Dhruv, Davit; Joshi, A.D.; Pandya, D.D.; Asokan, K.; Solanki, P.S.; Shah, N.A.
Abstract: In this communication, we report the dielectric response of pulsed laser deposition (PLD) grown Y0·95 Sr0·05 MnO3 (YSMO) manganite thin films (having two different thickness i.e. 200 & 300 nm) on single crystalline Nb:SrTiO3 (SNTO) substrates. These films were irradiated by 200 MeV Ag +15 ions with different ion fluence. Structural studies, using X–ray diffraction (XRD) measurement, reveal single phase nature without any detectable impurity within the measurement range studied. Atomic force microscopy (AFM) images reveal that grain size and grain boundaries are highly influenced by the SHI ion fluences and film's thickness. Variations in dielectric constant with frequency, ion fluence, and film thickness have been discussed in the context of structural strain at the film–substrate interface, defect density and structural disorder in films. To understand the dielectric response of all the films with the help of universal dielectric response (UDR) model while cole-cole plots have been studied for the relaxation mechanisms. Graphical abstract: Image 1 Highlights: Single phase 200 and 300nm YSMO manganite films were successfully grown on SNTO substrates using PLD technique. Irradiation using 200 MeV Ag +15 ions was performed with ion different fluence. The dielectric response is found to depend on frequency, ion fluence and film thickness. Role of structural disorder or lattice mismatch, defects and intrinsic properties of films has been understood.